A JURUDICAL ASSESSMENT OF THE BLUE ECONOMY'S CONTRIBUTION TO RURA COMMUNITIES' SUSTAINABLE DEVELOPMENT IN LIGHT OF NATURAL RESOURCES' POTENTIAL FOR GLOBAL APPLICATION BASED ON LOCAL WISDOM - Sutrisno, Endang; Gunawan, Moh sigit; Rahman, Alip; Permana, Deni Yusup; Dikrurrahman, Diky (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The blue economy, a sustainable development concept focused on the responsible use of marine resources, holds potential to empower sustainable development in rural society, particularly by using their natural resource potential for global reach while anchoring in local wisdom. This study analyses the juridical framework and implementation of the blue economy within Indonesia's rural society, exploring how blue economy can use their natural resources for global engagement while upholding local wisdom principles. Utilizing a normative legal research method, this study examines applicable legal provisions. Analysis reveals that while existing laws such as Law No. 27/2007 on Coastal Areas and Small Islands and Law No. 31/2004 on Fisheries touch upon the blue economy, the juridical regulation of the blue economy in Indonesia is still inadequate in scope and depth to support sustainable development in rural society. The existing regulations lack clarity and require strengthening, particularly on decentralized resource management within rural society, types of marine-based economic ventures, community participation in decision-making, and collaborative efforts between rural society, governments, and the private sector. To unlock the full potential of the blue economy for rural development, robust legal frameworks are necessary. This entails clarifying and strengthening existing regulations, with particular focus on empowering rural society through decentralized resource management and active participation in decision-making. Additionally, in fostering diverse marine-based economic activities and enhancing collaboration among rural society, governments and the private sector are crucial. Furthermore, enhancing rural society ability and knowledge concerning the blue economy, alongside continued support from the government and private sector, are vital for overcoming challenges in sustainable natural resource management.